FACTORS AFFECTING FIRM VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLE - Belinda, Belinda; Dewi, Sofia Prima (International Journal of Application on Economics and Business, 2023)
The goal of this research is to gather empirical evidence on the impact of profitability, liquidity, leverage, firm growth, firm size, and total assets turnover on firm value in manufacturing companies listed on the Indonesia Stock Exchange between 2017 and 2020, using dividend policy as a moderating variable. The purposive sampling method was utilized and a sample of 40 companies that met the criteria was collected. Secondary data is used in this study, which is subsequently analyzed using Eviews 12 with the Moderated Regression Analysis (MRA). The study's findings show that firm size (SIZE) affected firm value (Tobin’s Q). Firm value (Tobin’s Q) is unaffected by profitability (ROE), liquidity (CR), leverage (DER), firm growth (TAG), and total asset turnover (TATO). The relationship between profitability (ROE) and leverage (DER) on firm value (Tobin's Q) can be moderated by dividend policy (DPR). The relationship between liquidity (CR) and firm growth (TAG) on firm value (Tobin's Q) cannot be moderated by dividend policy (DPR).